Physical Activity Interventions for Behavioral and Cognitive Development in Children with Attention Deficit Hyperactivity Disorder - Agusniwati Agusniwati; Aynel Veyselova; Jayantha Kalansooriya (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to explore how structured physical activity and adaptive physical education can support behavioral, cognitive, motor, and social development in children with Attention Deficit Hyperactivity Disorder in a special needs school setting. Methodology: This study employed a qualitative case study design using a life story approach at Bina Anak Bangsa Special Needs School, Pontianak, Indonesia. Participants included three children with Attention Deficit Hyperactivity Disorder and six informants. Data were collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman interactive model of qualitative analysis. Main Findings: The findings showed that structured and consistent physical activities improved concentration, emotional regulation, motor coordination, and social interaction in children with Attention Deficit Hyperactivity Disorder. Individualized mentoring, guided play, and structured exercise routines were more effective than large-group activities. The results also indicated that continuous physical engagement helped stabilize behavior and enhanced children’s ability to follow instructions and participate in learning activities. Novelty/Originality of this study: This study highlights an integrated physical education and sports-based therapeutic approach for children with Attention Deficit Hyperactivity Disorder in special education settings. It emphasizes collaboration between teachers, coaches, parents, and psychologists in designing structured physical activity programs. The novelty lies in positioning adaptive physical activity as a coordinated non-pharmacological intervention supporting behavioral, motor, and cognitive development